The effect of Auxin Concentratioin and Planting Media Composition on The Growth and Yield of Straw Mushrooms (Volvariella volvaceae) - Novendra, Dimas Ihza; Setiyono; Nisak, Fauziatun; Patricia Sembiring, Susan Barbara; Arum, Ayu Puspita; Savitri, Dyah Ayu (Journal of Soilscape and Agriculture, 2025)
This research investigates the effect of auxin concentration and planting media composition on the growth and yield of paddy straw mushrooms (Volvariella volvacea). Using a completely randomized design (CRD), this study tested various treatment combinations of planting media composition consisting of 100% straw (M1), 75% straw + 25% tofu dregs (M2), and 50% straw + 50% tofu dregs (M3), as well as the addition of several auxin concentrations consisting of control or without auxin (K0), synthetic auxin 3 ml/L (K1), auxin 6 ml/L (K2), and auxin 9 ml/L (K3). The 100% straw planting medium (M1) resulted in the highest number of fruiting bodies, while the treatment combination of 75% straw and 25% tofu dregs with the addition of 6 ml/L auxin concentration (M2K2) is recommended to provide the best results for fruiting body diameter. In addition, the treatment combination of 75% straw and 25% tofu dregs with the addition of 9 ml/L auxin concentration (M2K3) produced the highest fruiting body weight. This research recommends the use of the right combination of media and auxin concentration for optimal paddy straw mushroom cultivation. The results of this study are expected to provide guidance for farmers in increasing the productivity of paddy straw mushrooms in Indonesia, especially in East Java, by utilizing organic waste as a nutrient-rich planting medium.